The European Pollen Information System (epi). Data bank (EAN), Web sites and forecasting - Jager, Siegfried (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
This paper presents the European Pollen Information System. It consists of three coherent units: the European aeroallergen database EAN, the public web portal www.polleninfo.org and a commercial branch „epi Ltd.”. Good cooperation of these three units results in the creation of precise pollination maps for various regions of Europe and effective transfer of information about pollen concentrations.